Seasonal constraints on the burial of organic carbon in the eutrophic Lake Taihu - Xu, Yanhong; He, Yuxin; Pang, Jiali; Sun, Yongge (Frontiers in Earth Science, 2023)
Eutrophication alters the function of lake ecosystems through phytoplankton blooms and is a major contributor to organic carbon (OC) burial in lakes worldwide. Although Lake Taihu is notable for its severe eutrophication yet low OC burial, why cyanobacteria-derived OC is ineffectively buried in the lake is unknown. Because seasonal hydrological and ecological dynamics in eutrophic lacustrine ecosystems would significantly modify the preservation and degradation behaviors of OC, seasonal variations in paired particulate samples from both the water column and surface sediment are critical in evaluating cyanobacteria-derived OC burial. In this study, we present the steroid results of water and sediments collected from Meiliang Bay in Lake Taihu across cyanobacteria-bloom and decay seasons (from May 2018 to June 2019) to investigate constraints on the seasonal burial of autochthonous and allochthonous OC. The results indicate that cyanobacteria contribute a considerable amount of OC to the water body in the cyanobacterial bloom season, while terrestrial OC becomes the main contributor during the cyanobacterial decay season. Although OC degradation occurs throughout the water column, substantially more OC degradation was observed at the water-sediment interface. The extensive degradation of OC in the bloom season eventually reverses the seasonal distribution characteristics of particulate OC in the water column, leading to less accumulation of OC under the background of higher cyanobacteria-derived OC input. The combined effect of OC bioavailability, temperature, oxygen exposure, and more importantly microorganism activities, accounts for much higher OC degradation rates in the bloom season. Similar phenomena were observed in subtropical shallow lakes with high primary productivity, suggesting that eutrophication might have a limited influence on OC burial when compared to other factors related to OC degradation.